THE EXCELLENCE CLASS LEARNING ATMOSPHERE OF ENGLISH FOR BIOLOGY II BIOLOGY EDUCATION STUDY PROGRAM FACULTY OF TEACHER TRAINING AND EDUCATION UNIVERSITY OF RIAU - Gusti Herdiah; Darmadi Ahmad; Firdaus L.N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
A descriptive study on learning atmosphere in the excellence BiologyTeacher’s Education Program, The Faculty of Teacher Training and Education,University of Riau has been conducted in the Even Semester of the AcademicYear 2012/2013. The objective was to find out the learning atmosphere inEnglish for Biology II courses. As much as eighteen students have been defined asthe total respondents by total sampling technique. Data of seven indicatorslearning atmosphere, namely: (1) cohesiveness, (2) lecture support, (3)involvement, (4) investigation, (5) task orientation, (6) cooperation, and (7)lecture equity obtained by questionnaire What Is Happening In this Class(WIHIC). The questionnaire was valid (rxy0,54>critical values0,3) dan reliabel(r110,96>critical values0,7). The questionnaires were directly ditributed to therespondents at the end of the semester. Supplements data were taken by videorecording during the learning process. All data were analyzed descriptively. Theresults showed that learning atmosphere English for Biology II were consideredvery conducive from aspects of cohesiveness of relationship between students,task orientation, cooperation and lecture equity. While the lecture support,involvement, and student investigations were considered is enough conducive. Inclonclusion, the learning atmosphere of English for Biology II by using Research-based teaching were considered was enough conducive. However, the learningatmosphere of English for Biology II is still needs to be improved in order tobecome very conducive, especially with regard to indicators of lecturer support,student involvement and investigation.Key Words : excellence biology teacher education programs, english for biologyII course, learning atmosphere, research-based teaching